2020
DOI: 10.1186/s12951-020-00610-9
|View full text |Cite
|
Sign up to set email alerts
|

Lipoplex-based targeted gene therapy for the suppression of tumours with VEGFR expression by producing anti-angiogenic molecules

Abstract: Background: The anti-angiogenic fusion protein RBDV-IgG1 Fc (RBDV), which comprises the receptor-binding domain of vascular endothelial growth factor-A (VEGF-A), has shown antitumour effects by reducing angiogenesis in vivo. This study used the cationic lipoplex lipo-PEG-PEI-complex (LPPC) to simultaneously encapsulate both the RBDV targeting protein and the RBDV plasmid (pRBDV) without covalent bonds to assess VEGFR targeting gene therapy in mice with melanoma in vivo. Results: LPPC protected the therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This study showed that LPPC combined DC MP and mAbs could be a good tool for regulating an individual’s immune responses by turning specific immune responses on or off. In addition, our previous results showed LPPC complexes could be safe in vivo because no obvious side effects were found in vivo treatment by histopathologic assay [ 15 , 17 , 21 ]. Moreover, to resolve the diversity and variation of MHC molecules and antigens in human population, LPPC/MP/Ab complexes showed remarkable potential and technological advances in human diseases such as cancers or autoimmune diseases for personalized precision immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study showed that LPPC combined DC MP and mAbs could be a good tool for regulating an individual’s immune responses by turning specific immune responses on or off. In addition, our previous results showed LPPC complexes could be safe in vivo because no obvious side effects were found in vivo treatment by histopathologic assay [ 15 , 17 , 21 ]. Moreover, to resolve the diversity and variation of MHC molecules and antigens in human population, LPPC/MP/Ab complexes showed remarkable potential and technological advances in human diseases such as cancers or autoimmune diseases for personalized precision immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…As described previously [ 21 ], the organs or tissues of the mice were formalin-fixed, paraffin-embedded and subsequently stained by using histochemical techniques. The tissue slides were observed under a light microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Active targeting can be achieved by incorporating or attaching ligands on the surface of the carrier that specifically bind to receptors present exclusively in the target tissue or cell [14][15][16]. Different types of molecules have been employed as active targeting moieties of non-viral nucleic acid delivery systems, such as antibodies [17] or antibody fragments [18], peptides [19] and carbohydrates [20]. However, it remains a challenge to design targeted carriers with high quality and good clinical translation and large-scale manufacturing capacity [21].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study proved that the LPPC delivery system enhanced the skin penetrability, drug accumulation ability, and e cacy of breast cancer therapies [21]. In addition, LPPC could enhance the cytotoxicity of the drug against different cancer cells [22], and LPPC provided their activities by adsorbing proteins and nucleotides without chemical modi cation [23,24]. Moreover, when combined with different adjuvants, the LPPC increased and switched immune responses [25].…”
mentioning
confidence: 99%